How do we recognize the child with OSAS?. Issue 2 (16th November 2016) - Joosten, Koen F.; Larramona, Helena; Miano, Silvia; Van Waardenburg, Dick; Kaditis, Athanasios G.; Vandenbussche, Nele; Ersu, Refika
Summary: Obstructive sleep‐disordered breathing includes a spectrum of clinical entities with variable severity ranging from primary snoring to obstructive sleep apnea syndrome (OSAS). The clinical suspicion for OSAS is most often raised by parental report of specific symptoms and/or abnormalities identified by the physical examination which predispose to upper airway obstruction (e.g., adenotonsillar hypertrophy, obesity, craniofacial abnormalities, neuromuscular disorders). Symptoms and signs of OSAS are classified into those directly related to the intermittent pharyngeal airway obstruction (e.g., parental report of snoring, apneic events) and into morbidity resulting from the upper airway obstruction (e.g., increased daytime sleepiness, hyperactivity, poor school performance, inadequate somatic growth rate or enuresis). History of premature birth and a family history of OSAS as well as obesity and African American ethnicity are associated with increased risk of sleep‐disordered breathing in childhood. Polysomnography is the gold standard method for the diagnosis of OSAS but may not be always feasible, especially in low‐income countries or non‐tertiary hospitals. Nocturnal oximetry and/or sleep questionnaires may be used to identify the child at high risk of OSAS when polysomnography is not an option. Endoscopy and MRI of the upper airway may help to identify the level(s) of upper airway obstruction and to evaluate the dynamic mechanics of the upper airway, especially in children with combined abnormalities.Pediatr Pulmonol. 2017;52:260–271. © 2016 Wiley Periodicals, Inc.